Burnout of Public Hospital Nurse: Does Work Stress and Workload Cause Prolonged Pysical, Emotional, and Mental Exaustion - Ni Made Dias Dinanda; I Gusti Ayu Manuati Dewi (International Journal of Management Research and Economics, 2024)
Burnout is a condition of prolonged physical, emotional and mental exhaustion. Burnout refers to a condition that the required resources and abilities are no longer sufficient to meet job requirements. The aim of this research is to analyze the role of work stress in mediating the influence of workload on burnout. This research was conducted at one General Hospital in Bali Province-Indonesia. The theory refer to this study is Attribution Theory. The number of samples in this study was 56 nurses which determined by using saturated sampling. Data collection was carried out through interview and distributing questionnaires. Path analysis was implemented to test the hypothesis. The findings show that workload has a positive and significant effect on burnout and job stress, job stress has a positive and significant effect on burnout and mediates the influence of workload on burnout partially. The implication of this study is empirically supports attribution theory, which explains a person's behavior based on three factors: specificity (behavior varying across different situations), consensus (similar responses from people in the same situation), and consistency (behavior remaining stable across actions). The practical implications of this research are expected to serve as considerations and feedback for leaders of public hospitals in addressing burnout by paying attention to the workload and work-related stress experienced by their nurses.